Influence of levothyroxine replacement on metabolic dysfunction-associated steatotic liver disease and dyslipidemia in subclinical hypothyroidism: insights from a randomized controlled study - Zainab Gaber Mahran; Salma Mokhtar Osman; Amira Abdelmawgod; Nahed A. Makhlouf; Elham Ahmed Hassan; Ehab F. Moustafa (The Egyptian Journal of Internal Medicine)
Abstract Background In recent years, there has been growing awareness of metabolic dysfunction-associated steatotic liver disease (MASLD) linked to hypothyroidism. However, insufficient data exists on how levothyroxine (LT4) replacement therapy impacts MASLD. We aimed to assess the effects of LT4 treatment on dyslipidemia and MASLD in patients with subclinical hypothyroidism (SCH). Methods In a randomized, controlled study, 230 patients with MASLD were screened for SCH, and 182 were diagnosed with SCH. Of these, 30 had significant SCH and 152 had mild SCH. All patients with significant SCH received LT4 therapy (significant SCH-LT4), while those with mild SCH were divided into two groups: 50 received LT4 treatment (mild SCH-LT4) and 102 did not (mild SCH-control). Results Significant improvements in hepatic steatosis severity were observed in the treated groups compared with the control. After LT4 treatment, MASLD prevalence decreased to 50% (p = 0.001) in the significant SCH-LT4 group and to 60% (p = 0.025) in the mild SCH-LT4 group. In the mild SCH-control group, MASLD prevalence improved slightly but non-significantly from 100 to 75% (p = 0.164). Compared to other groups, the significant SCH-LT4 group showed greater improvements in metabolic parameters, including weight, body mass index, total cholesterol, high-density lipoprotein cholesterol, and C-reactive protein, emphasizing the notable impact of levothyroxine. Conclusion This study highlights that LT4 treatment can significantly improve MASLD, dyslipidemia, and systemic inflammation in MASLD patients with SCH, particularly in those with significant SCH. These findings support the clinical use of thyroxine for managing MASLD and dyslipidemia in SCH patients.